Monitoring of Dilation Cracks and Vibrations Caused by Blasting Works at the Quarry of Mokra on Surrounding Construction Objects - Milan Mikolas; Roman Donocik; Jana Bartonova; Michal Vanek; Martin Mikolas (Communications - Scientific letters of the University of Zilina, 2012)
The quarry of Mokra, whose locality comprises administrative area of three communities, has cooperated with our Institute for a longer time, communicating with the authorities and people, as regards environmental safety and quality of living in the area. Monitoring of the conditions by continual measurements of dilation cracking and blasting works seismic effects has been an indispensable part of the collaboration.The measurement equipment was developed especially for the needs and condition of the quarry of Mokra, but can be used universally. This paper reports on technicalities of its development and experience of using it in practice.